ケイコウXセン ブンセキ ソウチ ヲ モチイタ テイキシャク ガラスビードホウ ニヨル ケイサンエン ガンセキ チュウ ノ シュヨウ ビリョウ キドルイ ゲンソ ノ テイリョウ ブンセキ - 隅田, 祥光; スダ, ヨシミツ; 本吉, 洋一; モトヨシ, ヨウイチ; Suda, Yoshimitsu; Motoyoshi, Yoichi (2011)
P(論文) 国立極地研究所設置の蛍光X線分析装置を用いた珪酸塩岩の定量分析法を更新した.測定元素にScとThを加え,Nbの測定にThの重なり補正を加えた.希土類元素とSiO_2の検量線に,カナダの標準試料(SY-3)と日本の標準試料(JCh-1)を加えた.また,分析値と同時にその誤差を算出するルーチンを確立させた.このことにより,得られた分析値の誤差を考慮した上での地球化学的解析への適用が可能となった.さらに,ロット番号の異なる融剤を用い分析を行ったところ,ある融剤から明らかなLaの混染が確認された.新たな融剤を使用する際は,必ず測定元素が分析誤差の範囲内で一定であることを確かめる必要がある. This paper reports on updates to the system used for quantitative analyses of major, trace, and rare earth elements in silicate rocks by X-ray fluorescence spectrometry (RIX3000) at the National Institute of Polar Research. We added Sc and Th to the list of measured elements, and the overlap coefficient of Th is used for the measurement of Nb. The geochemical standard samples SY-3 (Canada) and JCh-1 (Japan) have been added to the existing set of standard samples to improve the precision of analyses of SiO_2 and rare earth elements. Furthermore, we established a new method of evaluating the analytical error, making it possible to use analytical data for geochemical evaluation while considering the precision of the data. We also found that the analytical error may increase as a consequence of using a different lot number of the flux used in preparing the fused glass beads. It is therefore necessary to assess the background of the flux as well as the target elements, in terms of whether they are within the analytical error, before using a new flux. departmental bulletin paper